Fiscal Responsibility: A Critical Analysis of FRDL (2005) Pakistan (The Pakistan Development Review, 2012)
The term fiscal responsibility in financial dictionary is defined as “A balanced budget”. That is a budget wherein expenditures during a given period of time equal to revenues. The fiscal responsibility also includes a budget in which revenue is greater than the expenditures. Fiscal responsibility is achievable and most of the individuals in their private life practice fiscal responsibility. At individual level everybody knows that they have to live within the budget and usually they do not overspend. Usually overspending by individual results in bad crediting rating which one receives from their creditors due to non-payments or late payments of installments and thus denies future benefits to the person concern. Fiscal responsibility at national level implies that a government has a balanced budget and has sufficient revenue to pay for its all expenditures. There would be no overspending if government had a true balanced budget in each period. The economic future of a nation largely depends on the way fiscal responsibility is practiced. There is a direct link between budget deficit today and what nation can enjoy in future. Fiscal responsibility is crucial for a nation to remain prosperous and stronger in future. Fiscal responsibility will also determine what kind of future we are leaving to our children and grandchildren for the next 20 years and beyond. If the fiscal responsibility is not practiced the government would spend more money than its income and it borrows for the difference. If the money borrowed come from domestic savings or from domestic lenders the economy will have less money available for capital investment and future productivity growth rates and levels would be lower. If on the other hand deficit is financed by foreign organisation/country the country will be indebted with growing debt to the rest of the world, with growing interest costs which must be served every year. If we rely more on foreign sources to finance the resource gap the foreign ownership of our resources would grow and so has our dependences on the actions of foreign governments and investors.